Determining Risk Factors of Epilepsy in Children with Cerebral Palsy: A Retrospective Study - Ferda Gürkan; Sarenur Gökben; Hepsen Mine Serin; Sanem Yılmaz; Gül Aktan; Hasan Tekgül (Galenos Yayinevi, 2018)
Aim: The aim of this study is to determine the risk factors of epilepsy development in children with cerebral palsy. Materials and Methods: Data of 234 cerebral palsy patients treated at Ege University Pediatrics Department, Child Neurology Division between January 2008 and December 2015 were evaluated retrospectively. All patients were classified into two groups; Group I: cerebral palsy without epilepsy (n=116) and Group II: cerebral palsy with epilepsy (n=118). The clinical and laboratory findings of the groups were compared to each other, a p value of less than 0.05 was considered as statistically significant. Results: There was no significant difference between the two groups in terms of gender, gestastional age, birth type, birth weight, risk factors for cerebral palsy development (pre-/peri-/postnatal), duration of neonatal intensive care stay and the need for mechanical ventilation (p>0.05). The risk factors of epilepsy were determined as the following; the presence of neonatal convulsions, focal clonic and generalized tonic neonatal seizures, an abnormal baseline rhythm on neonatal electroencephalography (EEG), discharge from neonatal intensive care unit with at least one antiepileptic drug, spastic bilateral (tetraplegic) cerebral palsy, epileptic activity on the sixth month EEG, abnormal cranial magnetic resonance imaging findings, mental retardation, microcephaly and visual problems. Conclusion: Epilepsy is a common problem in children with cerebral palsy. Therefore, cases of cerebral palsy, especially those with the determined risk factors should be closely monitored for epilepsy in order to ensure a timely diagnosis and proper treatment.